Proficiency testing within Eurotransplant - Zoet, Yvonne M.; Heidt, Sebastiaan; van der Linden-van Oevelen, Marissa J. H.; Haasnoot, Geert W.; Claas, Frans H. J. (Frontiers in Genetics, 2024)
Eurotransplant is responsible for the international allocation of organs between 8 countries in Europe. All HLA laboratories affiliated to Eurotransplant must be EFI or ASHI accredited and must participate in the Eurotransplant external proficiency testing (EPT) program, organized by the Eurotransplant Reference Laboratory (ETRL). EPT within Eurotransplant has a long tradition, starting in 1978. The current EPT program consists of the following schemes: HLA typing including serology, CDC crossmatching, HLA-specific antibody detection and identification. Participants enter the results of laboratory tests using a web-based application. Assessed results are visible on the website. An additional component called "patient-based cases" runs since 2016. Results are summarized and published on the EPT website. Furthermore, these results are discussed during the annual extramural tissue typers meeting, which is organized by the ETRL. Thanks to this EPT program, the performance of all HLA laboratories affiliated to Eurotransplant can be monitored and corrected, if necessary. Because all affiliated laboratories are assessed in the same EPT program, where these laboratories show to be consistent in most of their results, the Eurotransplant EPT has proven to be an efficient tool to create a more uniform level of quality of histocompatibility testing within Eurotransplant.Eurotransplant is an international organ exchange organization founded in 1967 by prof. dr. Jon van Rood (van Rood 1967). Currently Eurotransplant consists of eight member states; Austria,